INFLUENCE OF COMPETENCE, COMPENSATION AND MOTIVATION ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS INTERVENING VARIABLE IN THE ENVIRONMENT OF INDONESIAN PROFESSIONAL CERTIFICATION AUTHORITY - Efendi, Suryono; Yusuf, Amirudin (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This research aims to determine the effect of competence, compensation and motivation on employee performance with job satisfaction as an intervening variable in the BNSP environment. Data was collected through filling out questionnaires by 134 BNSP employees with various work backgrounds. The analytical method used is quantitative with the Structural Equation Model (SEM) Path Analysis Approach. The results of the research revealed that competence and motivation had a positive and significant effect, while compensation had no significant positive effect on job satisfaction. The compensation variable proved to have a significant positive effect, while competence and motivation had no significant positive effect on employee performance. Job satisfaction directly has a positive effect on employee performance, this proves that if there is an increase in job satisfaction, then employee performance will also increase. Competence and motivation indirectly have a positive and significant effect, while compensation indirectly has a positive and insignificant effect on employee performance through job satisfaction. This research can be useful for policy makers at BNSP to assess the performance and job satisfaction of employees in their institutions. Keywords: Competence, Compensation, Motivation, Employee Performance, Job Satisfaction